2011
DOI: 10.1590/s0100-06832011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Variação na resistência tênsil de agregados em função do conteúdo de carbono em dois solos na região dos Campos Gerais

Abstract: (1) Recebido para publicação em julho de 2010 e aprovado em janeiro de 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
2
2
1
1
Order By: Relevance
“…The reduction either of TOC content, or of the physical fractions, increases the TS values. These results corroborate Tormena et al (2008b), Ferreira et al (2011), and Reis et al (2014b), who reported the increased TOC contents reduced the TS values, even in clayey soils.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The reduction either of TOC content, or of the physical fractions, increases the TS values. These results corroborate Tormena et al (2008b), Ferreira et al (2011), and Reis et al (2014b), who reported the increased TOC contents reduced the TS values, even in clayey soils.…”
Section: Resultssupporting
confidence: 89%
“…The average TS values obtained in the present study were higher than those reported by Imhoff et al (2002), Giarola et al (2003), Guimarães et al (2009), andFerreira et al (2011). According to Blanco-Canqui et al (2005), TS values are related to soil management and, in sugarcane production systems, the intense tillage prior to the crop establishing, besides the heavy machinery traffic for fertilization, and sugarcane transportation after manual harvesting, may have increased these values, as a result of increased soil density.…”
Section: Resultscontrasting
confidence: 74%
“…) when comparing the MA system with the TC system, while in the 10-20 cm layer the amount of lost CL decreased, the greatest loss being 0.61 g kg -1 from the MA system to the TC system, possibly more favorable to microbial activity and less protection of the CL inside smaller aggregates, similarly to results found by Bavoso et al (2010) and Ferreira et al (2011). A difference was found (p>0.05) in CL levels at the 0-5 cm and 5-10 cm depths between the MA system and the other systems (T5, T8, PA, TCP and TC).…”
Section: Agroforest System With Teak and Cocoa Tcsupporting
confidence: 77%
“…the no-till. Another relevant evidence is the inverse tendency of TOC in relation to TS ( Figure 4A), confirmed by Ferreira et al (2011) and Reis et al (2014).…”
Section: /9mentioning
confidence: 71%